COMPARISON OF PROXIMAL LEVELS IN PAPAYA JAM ACIDIFICATION AND NON-ACIDIFICATION MEDIA. - undri madidi; Srikit S. Nurkamiden; Alfian S.Abas (LPPM Universitas Bina Mandiri Gorontalo, 2022)
This processing aims to extend shelf life as well as increase the uniformity of products and add economic value. The research method used in this study is quantitative research, which is then analyzed using a statistical test of unpaired T.S. The results of the study obtained the proximal content of papaya jam non-acidification protein 10.36%, fat 8.05%, carbohydrates 67.75%, ash 17.8%, water 58.44% while in jam acidification in the results of protein 20.96%, fat 3.836, carbohydrates 78.57%, ash 25.6% and water 55.05%. From the results of the statistical test T- unpaired that the value of probality (sig 2-tailed) with the test T is not paired is 0.367. Because the probality value is greater than 0.05, H0 is received or in the data processing of the two samples does not differ significantly.